2023
DOI: 10.7554/elife.83710
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a conserved S2 epitope present on spike proteins from all highly pathogenic coronaviruses

Abstract: To address the ongoing SARS-CoV-2 pandemic and prepare for future coronavirus outbreaks, understanding the protective potential of epitopes conserved across SARS-CoV-2 variants and coronavirus lineages is essential. We describe a highly conserved, conformational S2 domain epitope present only in the prefusion core of β-coronaviruses: SARS-CoV-2 S2 apex residues 980–1006 in the flexible hinge. Antibody RAY53 binds the native hinge in MERS-CoV and SARS-CoV-2 spikes on the surface of mammalian cells and mediates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 95 publications
2
26
0
Order By: Relevance
“…2e) . Consistently, previous HDX-MS studies using the recombinant ectodomain of the spike protein with a prefusion stabilization (2P mutations) suggested the minor presence of an alternative conformation, in which S2 residues are solvent exposed, which can be targeted by nAbs, such as 3A3 and RAY53 22,23,25 . Therefore, in active viruses, the typical closed/packed prefusion conformation is dominant but the spike protein itself has ability to spontaneously transit to an open-trimer conformation.…”
Section: Mainsupporting
confidence: 79%
“…2e) . Consistently, previous HDX-MS studies using the recombinant ectodomain of the spike protein with a prefusion stabilization (2P mutations) suggested the minor presence of an alternative conformation, in which S2 residues are solvent exposed, which can be targeted by nAbs, such as 3A3 and RAY53 22,23,25 . Therefore, in active viruses, the typical closed/packed prefusion conformation is dominant but the spike protein itself has ability to spontaneously transit to an open-trimer conformation.…”
Section: Mainsupporting
confidence: 79%
“…This conserved pocket is shared among Omicron variants and is located at the critical functional hinge region involved in modulation S1-S2 opening motions. The experimental studies indicated that S dynamics may impact hinge epitope accessibility [46] and our results showed that this cryptic epitope may be accessible for ligand binding in the S trimer complexes with ACE2.…”
Section: Resultsmentioning
confidence: 62%
“…In this context, it may be worth noting the results of HDX-MS experiments suggesting partial destabilization not only near the S1/S2 cleavage site but also in the HR1 region which may be functionally required to promote fusion stage. Our results showed considerable stability of the highly conserved hinge epitope (residues 980-1010) located in the S2 region between the CH and HR1 segments that is involved in regulation of conformational changes required for fusion of the viral envelope [46].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations